Pyrin- and CARD-only Proteins as Regulators of NLR Functions - Le, Hongnga T.; Harton, Jonathan A. (Frontiers in Immunology, 2013)
Upon activation Nod-like receptors (NLRs) assemble into multi-protein complexes such as the NODosome and inflammasome. This process relies upon homo-domain interactions between the structurally related Pyrin and caspase-recruitment (CARD) domains and adaptor proteins, such as ASC, or effector proteins, such as caspase-1. Although a variety of NLRP and NLRC complexes have been described, along with their activating stimuli and associated proteins, less familiar are processes limiting assembly and/or promoting dissociation of NLR complexes. Given the importance of limiting harmful, chronic, inflammation, such regulatory mechanisms are significant and likely numerous. Proteins comprised of a solitary Pyrin domain (Pyrin-only) or CARD domain (CARD-only) posses an obvious potential ability to act as competitive inhibitors of NLR complexes. Indeed, both Pyrin-only proteins (POPs) and CARD-only proteins (COPs) have been described as regulators of caspase-1 and/or NLR-inflammasome activation and not surprisingly as factors mediating pathogenesis. Although clear examples of pathogen encoded POPs are currently limited to members of the poxviridae, the human genome likely encodes three POPs (POP1, POP2, and a potential POP3), of which only POP2 is known to prevent NLR:ASC interaction, and three COPs (COP/Pseudo-ICE, INCA, and ICEBERG), initially described for their ability to inhibit caspase-1 activity. Surprisingly, among eukaryotic species, POPs and COPs appear to be evolutionarily recent and restricted to higher primates, suggesting strong selective pressures driving their emergence. Despite the importance of understanding the regulation of NLR functions, relatively little attention has been devoted to revealing the biological impact of these intriguing proteins. This review highlights the current state of our understanding of POPs and COPs with attention to protein interaction, functions, evolution, implications for health and disease, and outstanding questions.